About the virtue in “Ikones of Polish princes and kings” by Jan Głuchowski - Słomka vel Słomiński, Krystian (Melusine. Old Literature and Culture, 2026)
“Vitae Regum Polonorum” by Klemens Janicki (Clemens Ianicius) (1516–1543) based on the Polish tradition of describing Polish rulers. This genre flourishes at the turn of the 16th and 17th centuries. The numerous translations and paraphrases of the Ianicius’ cycle were created then, including published in 1605, “Icones of Polish princes and kings” (“Ikones książąt i królów polskich”) by Jan Głuchowski (?–1604), who, based on the various rhetorical measures, repeatedly emphasized the role of virtue in the system of ruler’s values, and also formulated its definitions. It appears in the enumeration alongside other monarch attributes, but in different configurations. It also functions in the description of the ruler’s qualities as the culmination of other values. The definitions of virtue were built by Głuchowski using comparisons where he made tendecious associations, such as identification with a jewel. The highest value also appears in apophthegm formulations. Głuchowski most often drew on the proverbs that were popular in the literature at that time, modifying them to emphasize the content.